Liquidation of the Ukrainian Greek Catholic Church in 1946: Ideological and Propagandistic Component - Datskiv, Ihor; Kapitan, Larysa (Український історичний журнал, 2022)
The research purpose consists in the systemic analysis of the Soviet power and the state security bodies’ policy aimed at the liquidation of the Ukrainian Greek Catholic Church (UGCC) in the context of solving the national issue on the Western Ukrainian lands. The methodology. The complex of general scientific (analysis, synthesis, comparative, dialectical) and special (historical genetic, historical comparative, historical typological, problem chronological) methods of historical cognition was used. Scientific novelty. Owing to attracting new documents, the process of the UGCC liquidation by the Soviet structures in the Western Ukraine was analyzed, the measures aimed at levelling the influence of the Greek Catholic Church on the local Ukrainian population were clarified and the repressions to the Greek Catholic clergy were elucidated. Conclusions. After World War II, finding the Western Ukrainian territories under the Soviet influence, the Stalinist leadership faced the problem of pacifying and consolidating the local population who confessed Greek Catholicism. First of all, the measures envisaged the neutralization of the UGCC, which was considered as the Church “fifth column” of Vatican and its separate representatives maintained close contacts with the Ukrainian na-tionalists. The liquidation of the UGCC was conducted on the initiative of the USSR higher party leadership with the most active participation of the Soviet state security services that used various political and ideological measures of influence on clergymen and believers. The Russian Orthodox Church cooperating with the Peoples Commissariat of Internal Affairs (PCIA) was an active participant in liquidating the UGCC. The repressions against the priests and believers played an important role in this process. However, ideological propagandistic and repressive measures of the Soviet authorities and special services finally did not lead to the ultimate disappearance of the UGCC as it continued to function underground.